E-Readiness as a Tool for ICT Management in an E-University : The Case of UUM - Woon, Moong Vooi (2003)
This project applied the Database Application Life Cycle approach in database planning, design and administration for a web-based e-learning Readiness Survey and Index System (eLRSIS). Providing real-time information on eight key factors of e-Learning readiness (Psychological, Sociological, Environmental, Human resource, Financial, Technology, Equipment and Content) and the resultant Big-L index, eLRSIS is useful in the management of fast-changing ICT resources for e-learning provision and support. Results from eLRSIS could reduce guesswork and guide the decision makers at the University Teaching & Learning Centre of UUM in identifying targets and establishing corrective measures through change management programs, ultimately enhancing the performance of e-learning efforts and helps UUM in its quest of transforming into an e-university. Using UUM as case, a pilot-test with the prototype of eLRSIS had collected some data from the staff in the School of Economics (SE) and the School of Information Technology (STM). Preliminary results showed that overall the academic staff of SE and STM have fared weakly in terms of Psychological readiness, Financial readiness and Equipment rea.diness in e-learning, while scoring averagely in Sociological readiness, Human resource readiness, Environmental readiness, Technology readiness and Content readiness in e-Learning.